Integrasi Pendidikan Karakter pada Pembelajaran IPS Terpadu dalam berperilaku siswa kelas IV SD Inpres Padang Lampe - Muliana; Muh. Basri; Evi Ristiana (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The purpose of the study was to determine the integration of character education in IPS integrated subject toward to student behavior. This research uses descriptive approach with qualitative research methods. The research was held in SD Inpres Padang Lampe on March-April 2022. The informants in this study were the principal, teacher, 5 student and 2 parents of students. Methods of data collection using interviews, observation, and documentation. The analysis technique uses qualitative analysis. The results show that the implementation of character education consists of two components in terms of (1) thematic learning planning from fourth grade teachers in elementary school, the elements in lesson planning tend to have shown an integration of character education, can be seen from learning activity and learning method. (2) the implementation of integrating character education through self-development programs, namely spontaneous activities. Teachers use character education strategies through attitudes, which creating a conducive atmosphere and inculcating discipline. The support factors was school have provided a library for students to learning more and for teacher’s creativity in using various learning resources such as the social environment, electronic and printed media. Constraints not only come from the students themselves, but also the surrounding environment such as families, schools, communities and electronic and print media can affect student behavior.